A case of infection on the scion of grafted tomatoes by the root-knot nematode Meloidogyne javanica - Emmanuel A. TZORTZAKAKIS (Acta Agriculturae Slovenica, 2007)
This is a preliminary communication reporting on a case where the scion of a grafted tomato in a greenhouse crop of Crete became infected by the root–knot nematode  Meloidogyne javanica.